Achieving an Effective Physical Education Practicum in Schools: A Review - Simou Θεοφάνης; Papaioannou Αθανάσιος Γ. (Inquiries in Physical Education and Sport, 2013)
Generally, practicum is considered to be as one of the most important aspects of student teachers’ education (Farrell, 2008; Wright, 1999), since new teachers themselves judge school-based teaching as the most valuable part of their teaching preparation (LaMaster, 2001). The purpose of the current review was: (a) to detect the critical factors, which ensure the efficacy of a physical education (PE) practicum; (b) to describe the implementation of some PE practicum courses around the world; and (c) to make suggestions for a fully effective PE practicum. Among several practicum models in literature, the most recent conceptualization for student teachers education seems to be the articulated practicum, in which student, university and field supervisor cooperate together to achieve the objects of the practicum (Ryan, Toohey & Hughes, 1996). Practicum’s effectiveness can be influenced by many factors such as (a) the student teachers’ personal believes and their past experiences, (b) the cooperative relationship between pre-service and in-service PE teacher, and (c) the quality of supervision by university faculty. To sum up, the review showed that, in order to design a fully effective PE practicum there are some key points to take into consideration: (a) student’s pedagogical content knowledge should be addressed prior to schoolbased teaching; (b) several opportunities for closely supervised field experiences, under controlled conditions, (on campus or at schools) should be provided; (c) collaboration amongst student teachers, self-assessment and selfreflection should be promoted; and (d) cooperating in service PE teachers should be carefully trained to mentor their student teachers effectively.